Diffusely Increased Myocardial Extracellular Volume With or Without Focal Late Gadolinium Enhancement: Prevalence and Associations With Left Ventricular Size and Function. Issue 1 (January 2022) - Lundin, Magnus; Sörensson, Peder; Maret, Eva; Jenner, Jonas; Abdula, Goran; Nickander, Jannike; Themudo, Raquel; Caidahl, Kenneth; Kellman, Peter; Sigfridsson, Andreas; Ugander, Martin
Abstract : Purpose: Myocardial extracellular volume fraction (ECV) using cardiovascular magnetic resonance (CMR) can identify diffuse lesions not detected by late gadolinium enhancement (LGE). We aimed to determine the prevalence of increased ECV and its relation to other CMR findings. Materials and Methods: Consecutive patients (n=609, age median [interquartile range] 53 [39 to 66] y, 62% male) underwent CMR at 1.5 T. Focal lesions on LGE images were noted. ECV in regions without focal LGE findings defined diffuse changes. Pronounced increases in left ventricular (LV) end-diastolic volume index and LV mass index, and pronounced decreases in LV ejection fraction were defined as >3 SD from the sex-specific mean in healthy volunteers. Results: Of 609 patients without amyloidosis or hypertrophic cardiomyopathy, 8% had diffusely increased ECV and 5% of all patients had diffusely increased ECV without any focal LGE findings. Multivariate analysis showed that a pronounced increase in the LV end-diastolic volume index was associated with increased ECV ( P =0.001), but not LGE ( P =0.52). A pronounced decrease in LV ejection fraction was associated with the presence of LGE ( P <0.001), but not with increased ECV ( P =0.41). Conclusions: Eight percent of patients in this clinical cohort with known or suspected heart disease had diffusely increased ECV and 60% of these lacked focal LGE findings. LV size is independently associated with increased ECV, whereas systolic dysfunction is independently associated with LGE. This image-based clinical study demonstrates that ECV-CMR provides additional information negligibly related to the results of LGE imaging, and thereby increases the diagnostic yield of CMR.